Marketing Information Systems: Database, Software, and Marketing Strategy - Anom, Sulung; Ali, Hapzi (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
The aim of this research is to investigate the impact of electronic business information systems (ECRM) on the online market of business information systems. Limited to consulting, marketing and advertising buying and selling, we need a database to make your business easier, efficient, fast and easy and sell regardless of distance or time. That can happen. They can do it. For people, the importance of marketing information is that they can buy products online quickly and easily. After creating a product database, customers can easily register in the desired product database and pay for the product via bank transfer. Qualitative analysis was used in this research. The research results show that: 1) e-commerce has an effect on consumer information; 2. E-CRM affects customer information; and 3) collection of information that affects customer data.